Repercussions generic skills portfolio to build the educational experience on the students and paintings in their steps fractals (2014)
ABSTRACT: he main objective of this research is to develop a catalog of generic competencies that help student to fully form for an efficient participation in the classroom promoting the contents to be transmitted for a teaching curriculum and that the student can develop the intellectual capacities of the abstract and specific thought. So it is also expected that teachers awaken the intellectual curiosity of children, encouraging them taste, habit for knowledge, permanent and autonomous knowledge (learn to learn), implementing resources and didactic techniques, close to the contemporary pedagogical approaches and motivation of knowledge, using information and communication technologies.